Comparative Evaluation of Ion Release and Uptake of Fluoride Varnish Containing Dicalcium Phosphate Dihydrate and Casein Phosphopeptide-Amorphous Calcium Phosphate – An Experimental Approach. - Patil Aishwarya Bhavesh; Arun M Xavier; Balagopal Varma R; Suresh Kumar J; Parvathy Kumaran; Malini Venugopal; Nishna Thankappan (The Bioscan, 2024)
The effectiveness of fluoride varnish may be restricted due to inadequate bioavailability of phosphate and calcium ions in the oral cavity. Dicalcium phosphate dihydrate and Casein phosphopeptide–amorphous calcium phosphate have exhibited ability to enhance absorption of calcium and fluoride. The present study aims to compare the remineralization potential of fluoride varnishes containing DCPD and CPP-ACP. Materials and Method: The ion release, precipitation and surface microhardness of enamel blocks were compared following topical application of various Floride varnishes. Thirty enamel blocks were divided into 3 groups following randomization that included: NaF varnish (Group A), CPP-ACP NaF varnish (Group B) and DCPD- NaF varnish (Group C). Pre- and post-treatment microhardness was evaluated using Vickers Microhardness Tester. UV-Vis Spectroscopy assessed the fluoride release at 2 hrs, 4 hrs and 6 hrs. The uptake of fluoride, calcium and phosphates were determined using SEM-EDX. The statistical significance was tested with One-way ANOVA variance for normality followed by post-hoc tests (p ≤ 0.05). Results: All the groups showed statistically significant increase in microhardness post-treatment (Group A: p=0.03, Group B, C: p=0.00). The mean increase in VHN was Group B (53.67) > Group C (34.75) > Group A (27.40). No significant difference in the F release was noted over time (p=0.00). The fluoride release over all three time intervals was Group C > Group B > Group C. Fluoride, Calcium and Phosphates showed highly significant differences between groups (p=0.00) with Group C > Group A> Group B. Conclusion: The novel NaF-DCPD Varnish displayed a promising remineralization potential, however it cannot be conclusively considered to be superior to the commercially available NaF-CPP ACP Varnish. Further in-vivo investigations need to be undertaken to determine the efficacy of NaF-DCPD varnish to determine its feasibility in clinical practice.